MOOD TYPES IN EDUCATION AND HEALTH CAMPAIGN MILLENASIA PROJECT VIDEO "BE THE FUTURE" BY UNESCO (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
As social individuals, people live with language to communicate ideas, emotions, and information daily. That is why there are a bunch of ways to accommodate peopleâ€™s needs. One of them is a song as a special communication media with special addition of harmony attracts people to do more communication, especially here song is used for a campaign action. As a communication tool, song should have a mood element to deliver a particular utterance such as state, point, and ask depending on the theme of the song. Therefore, this research aims to analyze the type of mood and which dominates in the Millenasia project video â€œBe the Futureâ€ by Dreamcatcher, IN2IT, and Alexa as the delegation of education and health campaign held by UNESCO. This research tends to use a descriptive qualitative research method to analyze all types of mood included in that video by using Butt theory. The result of the analysis showed that there are three types of moods such as 32 declarative moods, 31 imperative moods, and 2 interrogative moods. In brief, the most frequent moods are declarative moods and imperative moods showed that this video including song was made to influence someone as the real purpose of campaign action.